(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
This paper analyzes his short story, ’the Prophet’s Hair’as an investigation of the status of the notorious in Rushdie’s composing: thatis, his fictional medication of pictures, images or statements which conveyconspicuously hallowed meanings. It delineates the degree to which the symbol’simportance is resolved by the setting in which it is set, and its capacity tosubvert and destabilize the points of confinement put upon its importance bysuch an encircling. It will fight that the political suggestions of hybridityin Rushdie’s work are best grasped in wording of this engagement with andrecontextualization of famous material, which is not just a ’bearing over’s, inthe expressions of Rushdie’s article ’imaginary Countries’, and yet a burglary,and a demonstration of willful contemptuousness.